Impact of the oxbow lakes project II: on participant households - BRAC (© BRAC, 2016)
1. Introduction 2. Methodology 3. Socio-economic characteristics of the participant households 4. Material well-being of the participant households 5. Displacement of the fishermen 6. Oxbow lake management